Optimizing Wound Care after Surgery of the Head and Neck: A Review of Dressing Materials - Lohuis, Peter J.F.M.; Maldonado-Chapa, Felix; Santos-Santillana, Karla M.; Filipović, Boris; Dirven, Richard; Karakullukcku, M. Baris; Karssemakers, Luc; Schreuder, Willem H.; Zuur, Charlotte L.; Timmermans, Jacqueline (Facial Plastic Surgery, 2023)
Wound healing is a complex biological process subject to complications that might jeopardize the patient's postoperative care. Appropriately approaching surgical wounds after head and neck surgery positively influences the quality and speed of wound healing and increases patient comfort. A large variety of dressing materials currently exist that allow the care of different types of wounds. Nevertheless, there is limited literature on the most suitable types of dressings after head and neck surgery. The objective of the present article is to review the most commonly used wound dressings, their benefits, indications, and disadvantages, and to provide a systematic approach for wound care within the head and neck. The Woundcare Consultant Society distinguishes wounds into three groups: black, yellow, and red. Each type of wound represents distinctive underlying pathophysiological processes with unique needs. Utilizing this classification along with the TIME model allows a proper characterization of wounds and the identification of potential healing barriers. This evidence-based and systematic approach can facilitate and guide the head and neck surgeon in selecting a wound dressing upon acknowledging their properties, which are herein reviewed and exemplified with representative cases.
Keywords: wound care; surgical wounds; head and neck; dressing material